A systematic review on dry-land strength and conditioning training on swimming performance - Amaro, N. M.; Morouço, P. G.; Marques, M. C.; Batalha, N.; Neiva, H.; Marinho, D. A. (Science & Sports, 2019)
Objectives: The objective of this review was to examine the effects of dry-land strength and conditioning (S&C) training on swimming, and starts and turns performances. News: S&C training is a common practice in swimming aiming to enhance performance or to prevent injuries. However, studies regarding the effects of S&C on swimming performance are scarce; the influence of age, gender or competitive level is even scarcer. Prospects and projects: After a structured literature search, sixteen studies were included in the current review. Of those, seven did not report any positive or negative effects on swimming performance. Contrarily, most studies with positive effects were conducted with older swimmers whereas maximal strength was the most effective methodology for improving swimming performance. S&C plyometric training is suggested to be the most effective method to improve starts and turns. Future Randomized Controlled Trials should be conducted to explore the effects of S&C induced by age and gender, on different swimming distances and techniques, and long-term training effects. Conclusion: It is recommended that S&C training should be based on maximal strength, ranging from six to twelve weeks of 2 to 4 sessions per week (approximately 24 sessions altogether). In each session, coaches should vary from 2 to 3 sets and 3 to 5 repetitions, according to prescribed intensity. Rest intervals should range between 2 to 5minutes and the intensity should be from 80 to 90% of 1RM. Particularly regarding improving starts and turns, a S&C training regime ranging from 6 to 8 weeks and with 2 sessions per week is suggested. In each session, swimmers should perform between 1 and 6 sets and 1 and 10 repetitions, according to the established intensity. Rest between sets should range from 60 to 90seconds. The swimmers in the included studies are mostly men which do not allow to say if the recommendations made are gender-dependent.